Cooperative translational control of polymorphic BAFF by NF90 and miR-15a. Issue 22 (1st October 2018) - Idda, M Laura; Lodde, Valeria; McClusky, Waverly G; Martindale, Jennifer L; Yang, Xiaoling; Munk, Rachel; Steri, Maristella; Orrù, Valeria; Mulas, Antonella; Cucca, Francesco; Abdelmohsen, Kotb; Gorospe, Myriam
Abstract: Polymorphisms in untranslated regions (UTRs) of disease-associated mRNAs can alter protein production. We recently identified a genetic variant in the 3′UTR of the TNFSF13B gene, encoding the cytokine BAFF (B-cell-activating factor), that generates an alternative polyadenylation site yielding a shorter, more actively translated variant, BAFF-var mRNA. Accordingly, individuals bearing the TNFSF13B variant had higher circulating BAFF and elevated risk of developing autoimmune diseases. Here, we investigated the molecular mechanisms controlling the enhanced translation of BAFF-var mRNA. We identified nuclear factor 90 (NF90, also known as ILF3) as an RNA-binding protein that bound preferentially the wild-type ( BAFF-WT mRNA) but not BAFF-var mRNA in human monocytic leukemia THP-1 cells. NF90 selectively suppressed BAFF translation by recruiting miR-15a to the 3′UTR of BAFF-WT mRNA. Our results uncover a paradigm whereby an autoimmunity-causing BAFF polymorphism prevents NF90-mediated recruitment of microRNAs to suppress BAFF translation, raising the levels of disease-associated BAFF.